An Application of Preference-Inspired Co-Evolutionary Algorithm to Sectorization - Ozturk, Elif Goksu; Pedro Rocha; Sousa, F.; Lima, Maria Margarida; Rodrigues, Ana Maria; Ferreira, José Soeiro; Nunes, Ana Catarina; Lopes, Isabel Cristina; Oliveira, Cristina Teles (2nd International Conference Innovation in Engineering, ICIE 2022, 2022)
Sectorization problems have significant challenges arising from the many objectives that must be optimised simultaneously. Several methods exist to deal with these many-objective optimisation problems, but each has its limitations. This paper analyses an application of Preference Inspired Co-Evolutionary Algorithms, with goal vectors (PICEA-g) to sectorization problems. The method is tested on instances of different size difficulty levels and various configurations for mutation rate and population number. The main purpose is to find the best configuration for PICEA-g to solve sectorization problems. Performancemetrics are used to evaluate these configurations regarding the solutions’ spread, convergence, and diversity in the solution space. Several test trials showed that big and medium-sized instances perform better with low mutation rates and large population sizes. The opposite is valid for the small size instances.